PENINGKATAN AKTIVITAS BELAJAR SISWA PELAJARAN ILMU PENGETAHUAN SOSIAL MENGGUNAKAN TIPE JIGSAW DI SEKOLAH DASAR - Rita, Rita; Asran, Mastar; Margiati, K.Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to describe the improvement of students’ learning activity on learning Ilmu Pengetahuan Sosial using jigsaw type. The method of this research is classroom action research with participation collaborative charachteristics. The subject of this research is fourth grade students of SD Negeri Trans Marong. Technique of data analysis used is direct observation and documentation technique. The tool of data collecting is IPKG I observation sheet and IPKG II observation sheet. Based on the data analysis, in the first cycle, teacher’s ability on planning is 3.21, and 3.51 in the second cycle II, and 3.74 in the third cycle. Meanwhile, teacher’s ability on implementing is 3.19 in the first cycle, 3.50 in the second cycle and 3.75 in the second cycle. The students’ learning activity gets 70.83% in the first cycle, 73.96 % in the second cycle, and 79.17% in the third cycle. From the first until third cycle, students’learning activity improve 8.34 point. In conclusion, there is an improvement on students’ learning activity in learning Ilmu Pengetahuan Sosial using jigsaw type.  Keywords : Improvement, Learning Activity, Ilmu Pengetahuan Sosial, Jigsaw Type